2017
DOI: 10.1186/s12906-017-1639-x
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Arabic & Islamic medicine: validation and empirical assessment of a conceptual model in Qatar

Abstract: BackgroundEvidence indicates traditional medicine is no longer only used for the healthcare of the poor, its prevalence is also increasing in countries where allopathic medicine is predominant in the healthcare system. While these healing practices have been utilized for thousands of years in the Arabian Gulf, only recently has a theoretical model been developed illustrating the linkages and components of such practices articulated as Traditional Arabic & Islamic Medicine (TAIM). Despite previous theoretical w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 21 publications
0
38
0
4
Order By: Relevance
“…Cupping is an ancient method that has been used worldwide. From ancient Egypt to the Han Dynasty in China [9,10], and from Hippocrates in Greece to the early Islamic period [11,12], there have been numerous descriptions of cupping treatments for various diseases. Cupping is currently used to treat a wide range of medical conditions [13,14], and randomized controlled trials (RCTs) have confirmed the efficacy of cupping for certain pain-related diseases such as osteoarthritis of the knee and chronic low back pain [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Cupping is an ancient method that has been used worldwide. From ancient Egypt to the Han Dynasty in China [9,10], and from Hippocrates in Greece to the early Islamic period [11,12], there have been numerous descriptions of cupping treatments for various diseases. Cupping is currently used to treat a wide range of medical conditions [13,14], and randomized controlled trials (RCTs) have confirmed the efficacy of cupping for certain pain-related diseases such as osteoarthritis of the knee and chronic low back pain [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…To use honey as a medicine is general practice in sub-Saharan Africa and was so recurrent in my interviews, that countries and ethnic groups need not to be mentioned. In the Arabic and Islamic world one has to take into account that the prophet Mohammed considered a drink of honey as one of the methods in curing an illness (38). It seems to cure most ailments and the following were mentioned: allergy, anaemia, chest pain (often with eggs), bad cough (used with lime), whooping cough, asthma, u, high fever (as ointment), in uenza, tonsillitis, earache [also mentioned as remedy in the Qur'an (39; p. 89)], hiccup, tetanus, measles, as an ointment for dermatological problems (such as boils, sores, scabies, ulcers, leishmaniasis wounds, insect bites), jaundice, eye problems, cancer, epilepsy in Sudan (40), tiredness, stomach problems, (amoebic) dysentery, colic, constipation, diabetes, hypertension, palpitations, haemorrhoids, intestinal worms, poisoning (as antivenom), to purify the blood.…”
Section: Honeymentioning
confidence: 99%
“…Cupping is an ancient method that has been used worldwide. From ancient Egypt to the Han Dynasty in China [10,11], and from Hippocrates in Greece to the early Islamic period [12,13], there have been numerous descriptions of cupping treatments for various diseases. Cupping is also currently used to treat a wide range of medical conditions [14,15], and randomized controlled trials (RCTs) have confirmed the efficacy of cupping for certain pain-related diseases such as osteoarthritis of the knee and chronic low back pain [16,17].…”
Section: Introductionmentioning
confidence: 99%